Pengaruh Pemakaian Alat Ortodontik Cekat Terhadap Keparahan Periodontitis Pada Ibu Hamil Di RS PKU Muhammadiyah Surakarta - Agustina, Bhintari, drg. Edi Karyadi, M.M, drg. S.E. Yuletnawati, M.DSc (2016)
Background: Pregnancy caused the changes of women, such as physical and physiological changes that influenced the health of oral cavity, especially periodontal tissues. Periodontitis is a disease that characterized by inflammation of periodontal tissues, which involved loss of connective tissues attachment to the cementum and formed pockets. Increasing concentrations of estrogen and progesterone hormone caused gingival became more sensitive to plaque and can be aggravated by using fixed orthodontic appliance. Fixed orthodontic appliance is a tool that stick to the teeth and cannot be removed and installed by the user. Objective: This study aims to prove the effect of using fixed orthodontic appliances on the severity of periodontitis on pregnant women in Surakarta. Methods: This study was an observational analytic study, held on March until April 2016 and used cross sectional method, this study got 30 pregnant women who are willing to be the subject of research consist of 15 pregnant women who didnot use fixed orthodontic appliance and 15 pregnant women who used fixed orthodontic appliance, for sampling using purposive sampling method. The main measuring tool that used was standard WHO periodontal probes and periodontal disease index (PDI) to know the severity of periodontitis. The results that obtained then tested using SPSS 20.0 for windows with crosstabulation and analyze data using chi-square test with confidence interval 95% and the value of p <0.05 was considered significant.Crosstabulation data showed that a group of pregnant women who didnot use fixed orthodontic appliance 36.7% mild periodontitis, 13.3% moderate periodontitis and a group that use fixed orthodontic 10.0% mild periodontitis and 40.0% moderate periodontitis. The results of chi-square test showed there was a connective effects of fixed orthodontic appliances on the severity of periodontitis on pregnant women in Surakarta showed the significant value 0.003. Conclusion: The conclusion of this study, there was the effect of using fixed orthodontic appliance to periodontitis severity studies on pregnant women in Surakarta. Key words: estrogen and progesterone hormones, fixed orthodontic appliance, Periodontitis , Pregnant women.